2016
DOI: 10.1007/s12011-015-0589-8
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Deficiency Attenuates Chicken Duodenal Mucosal Immunity via Activation of the NF-κb Signaling Pathway

Abstract: Selenium (Se) deficiency can cause intestinal mucosal inflammation, which is related to activation of nuclear transcription factor kappa-B (NF-κB) signaling pathway. However, the mechanism of inflammatory response in chicken duodenal mucosa caused by Se deficiency and its relationship with the NF-κB signaling pathway remain elusive. In this study, we firstly obtained Se-deficient chickens bred with 0.01 mg/kg Se and the normal chickens bred with 0.4 mg/kg Se for 35 days. Then, NF-κB signaling pathway, secretor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…Furthermore, Se involves in virtually all aspects of immune function (reviewed by Dalgaard et al (2018) and Nabi et al (2020)). Se deficiency influences unfavourably immune cell development and differentiation in both innate and acquired immune defences, as manifested with atrophy of lymphoid tissues, decreased number of T and B lymphocytes, and impaired immune functions including lymphocyte proliferation, pro-inflammatory cytokine secretions, antibody responses, macrophage phagocytic activity and specific functions of heterophils (Liu et al 2016;Yang et al 2016;Pan et al 2018;Yiming et al 2020). However, the impact of Se supplementation on the immune system varies under different environments (Habibian et al 2014;Rama Rao et al 2016) and is highly influenced by the level and source of dietary Se (Boostani et al 2015;Wang et al 2016;Shabani et al 2019;Shojadoost et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Se involves in virtually all aspects of immune function (reviewed by Dalgaard et al (2018) and Nabi et al (2020)). Se deficiency influences unfavourably immune cell development and differentiation in both innate and acquired immune defences, as manifested with atrophy of lymphoid tissues, decreased number of T and B lymphocytes, and impaired immune functions including lymphocyte proliferation, pro-inflammatory cytokine secretions, antibody responses, macrophage phagocytic activity and specific functions of heterophils (Liu et al 2016;Yang et al 2016;Pan et al 2018;Yiming et al 2020). However, the impact of Se supplementation on the immune system varies under different environments (Habibian et al 2014;Rama Rao et al 2016) and is highly influenced by the level and source of dietary Se (Boostani et al 2015;Wang et al 2016;Shabani et al 2019;Shojadoost et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In commercial broilers, selenium deficiency reduced the content of soluble IgA in the duodenal mucosa and increased the level of pro-inflammatory cytokine IL-1β. In contrast, anti-inflammatory cytokines, such as TGF-β1 and IL-10, were significantly inhibited (Liu et al, 2016). In present study, the HMSeBA group increased the protein FIGURE 5 | Heat map of correlation analysis between serum cytokines and microorganisms at the phylum level.…”
Section: Discussionmentioning
confidence: 45%
“…Low Se content may also affect intestinal mucosal immunity and in commercial broilers, deficiency was shown to reduce soluble IgA amounts in the duodenal mucosa and increase levels of pro-inflammatory cytokines interleukin-1β (IL-1β), IL-17A and interferon gamma (IFN-γ). In contrast, anti-inflammatory cytokines, such as TGF-β1 and IL-10, were significantly suppressed (Liu et al, 2016).…”
Section: Innate Immunitymentioning
confidence: 89%
“…Chen et al (2012) concluded that differences in morbidity and severity of PMWS observed in different pig farms may be related to variation in oxidative stress and that selenium has a potential role in the control of PCV2 infection. Furthermore, dietary Se and vitamin E mitigated the impacts of heat stress on intestinal barrier integrity, associated with a reduction in oxidative stress in growing female pigs (Liu et al, 2016). On the other hand, after a bacterial induced acute-phase reaction using Actinobacillus pleuropneumonia, Humann-Ziehank et al (2014) concluded that Se status was only marginally affected by the infection, and GPX activity in blood and liver remained unaffected.…”
Section: Pig Diseasesmentioning
confidence: 99%